In vitro Antibacterial Effect of Medicinal Plants Against Multidrug Resistant Gram Negative Bacteria (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The aim of this work was to determine the antibacterial activity of methanol extract of herbal plants against the Multidrug resistant (MDR) Gram negative bacteria isolated from clinical samples.Methods: Gram negative bacteria isolated from various clinical samples were processed for antibiotic susceptibility test by modified Kirby-Bauer disc diffusion method and MDR bacteria were selected. Methanol extracts of six different medicinal plants Acorus calamus (bojho), Ocimum sanctum (tulsi), Azadirachta indica (neem), Cinnamomum tamala (tejpatta), Aloe vera and Zanthoxylum alatum (timur), were tested for antibacterial activity against the selected MDR bacteria by agar well diffusion method.Results: From clinical samples, 8 different MDR Gram negative bacteria isolated were Escherichia coli, Klebsiella pneumoniae, Klebsiella oxytoca, Citrobacter spp., Proteus mirabilis, Proteus vulgaris, Acinetobacter spp. and Pseudomonas spp. with E. coli dominated the number. Out of six medicinal plants extracts, Z. alatum, C. tamala and Ocimum sanctum were found to be effective with zones of inhibition ranging from 9-13 mm. The medicinal plants with antibacterial activity can be an alternative source of medicine against MDR Gram negative bacteria.Conclusion: Several herbal plants extracts exhibit antibacterial activity against MDR Gram negative bacteria. Antibacterial activity of plant extracts can vary with type of plant and extraction methods. Thus, for optimal benefit of plant extract, an appropriate extraction method and use of purified product is essential.